Learning from supervisor negative gossip: the reflective learning process and performance outcome of employee receivers - Bai, Yun; Wang, Jie; Chen, Tingting; Li, Fuli (SAGE Publications Ltd, 2019)
Workplace gossip is generally viewed as a deviant behavior that negatively affects the work outcomes of employees. However, we argue that this negative view is incomplete. Drawing on the cultural learning perspective of gossip and social learning theory, we examine how the job performance of employee receivers benefits from supervisor negative gossip through reflective learning. On the basis of multi-source, cross-sectional designs, Studies 1 and 2 consistently find that supervisor negative gossip facilitates employee receiver reflective learning and subsequent job performance when controlling for two sets of theory-relevant variables. Study 3, which has a multi-source, cross-lagged panel design, provides further evidence of the directional relationship from supervisor negative gossip to employee receiver job performance through reflective learning. The findings of the three separate field studies support the positive effect of supervisor negative gossip on employee receivers from a learning perspective. We discuss the theoretical and practical implications of these findings in terms of how employee receiver job performance can benefit from workplace negative gossip.